2022
DOI: 10.1111/nph.18296
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine metabolism genes in diatoms are not regulated by thiamine despite the presence of predicted riboswitches

Abstract: Thiamine pyrophosphate (TPP), an essential co-factor for all species, is biosynthesised through a metabolically expensive pathway regulated by TPP riboswitches in bacteria, fungi, plants and green algae. Diatoms are microalgae responsible for c. 20% of global primary production. They have been predicted to contain TPP aptamers in the 3 0 UTR of some thiamine metabolism-related genes, but little information is known about their function and regulation.We used bioinformatics, antimetabolite growth assays, RT-qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Similar results were found in a study of the microbial community in the North Atlantic Ocean, and thiamine-related compounds were positively correlated with bacterial production ( 37 ). However, a recent study showed that thiamine metabolism genes in diatoms cannot be regulated by exogenous thiamine ( 38 ). Herein, the thiamine metabolic genes were significantly downregulated in some genera with exogenous thiamine ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in a study of the microbial community in the North Atlantic Ocean, and thiamine-related compounds were positively correlated with bacterial production ( 37 ). However, a recent study showed that thiamine metabolism genes in diatoms cannot be regulated by exogenous thiamine ( 38 ). Herein, the thiamine metabolic genes were significantly downregulated in some genera with exogenous thiamine ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that EukCatA played critical roles in voltage-regulated Ca 2+ signaling and Ca 2+ -dependent gliding motility and potentially served as an alternative mechanism of 4D-Ca v /Na v channels in pennate diatoms [ 214 ]. The CRISPR/Cas9 method was employed to investigate the thiamine metabolic process in P. tricornutum [ 215 ]. The knockout of the HMP-P synthase ( THIC ) gene ( PtTHIC ) and thiamine-related proteins SSSP gene ( PtSSSP ) indicated that the PtTHIC was essential for thiamine biosynthesis while PtSSSP served in thiamine uptake [ 215 ].…”
Section: Crispr/cas In Marine Algal Researchmentioning
confidence: 99%
“…The CRISPR/Cas9 method was employed to investigate the thiamine metabolic process in P. tricornutum [ 215 ]. The knockout of the HMP-P synthase ( THIC ) gene ( PtTHIC ) and thiamine-related proteins SSSP gene ( PtSSSP ) indicated that the PtTHIC was essential for thiamine biosynthesis while PtSSSP served in thiamine uptake [ 215 ].…”
Section: Crispr/cas In Marine Algal Researchmentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org degradation could induce increased lipid yields in different microalgal species (Nguyen A. D. et al, 2020;Chang et al, 2020). Several other studies were also successful in implementing CRISPR/Cas9 to increase the production of different carotenoids in Dunaliella salina (Hu et al, 2021); and in Chlamydomonas reinhardtii (Baek et al, 2016), to improve the thermal tolerance of Tetraselmis suecica (Xu J. et al, 2020), and to investigate gene function in Phaeodactylum tricornutum (Hao et al, 2022;Llavero-Pasquina et al, 2022). Overall, CRISPR/ Cas9 has been successfully applied on many other algae species to improve their biomass productivities, tolerances to abiotic stressors, or increase lipid content, or that of other biomolecules and value-added products (Kumar et al, 2020;Jeon et al, 2021;Wang et al, 2021).…”
Section: Crispr/cas9mentioning
confidence: 99%